(untitled) (Faridpur Medical College Journal, 2025)
Hemorrhoidal disease is a very common anorectal condition affecting thousands of people around the world. Patients have been offered medical therapy as a first-line treatment, with procedural interventions reserved for those with refractory symptoms. Conventional excisional hemorrhoidectomy is an effective treatment for hemorrhoids, but their drawback is severe postoperative pain and other complications. Laser energy is a novel technique that is being increasingly used in treating hemorrhoids. The aim of our study is to analyze the feasibility and efficacy of “laser hemorrhoidoplasty” in patients with grade II to IV hemorrhoids, which reflects our initial experience with this minimally invasive treatment. This prospective observational study was conducted in Faridpur Medical College Hospital, Faridpur, and some private hospitals of the city. Total 100 cases were operated on over one and a half years. All operations were performed by the principal author. A visual analog scale 0–10 was used to assess postoperative pain. All patients were followed up 3 years postoperatively. A common postoperative complication was per rectal seromucoid discharge, which resolves over time. No spontaneous bleeding was reported postoperatively. Post-operative pain was minimum and as the day passed, 98% of patients returned to their normal activity within a week. Only 7% of patients required oral NSAID at 2 weeks after surgery. Submucosal hematoma is the only peroperative complication. The procedure was almost bloodless. During first and second year follow-up, there was no recurrence. Only 2 patients (2%) came back at the end of the third year with recurrence. LHP is very safe and associated with very few complications when performed methodically with judicious application of laser energy at the proper tissue plane. Mucopexy gives additional benefit in terms of reducing the pile mass and possibly reducing the recurrences. Faridpur Med. Coll. J. 2025;20(1):13-18